The Quality Analysis of Final Examination Test in Biology Education Major - Kurnia Ningsih (JETL (Journal of Education, Teaching and Learning), 2017)
The goal to be achieved in this study is to analyze the quality of the exam questions even semester 2015/2016 school year in Biology Education program. This research uses descriptive method. With the object of research about the exam semester even the academic year 2015/2016 in Biology Education program. Exam analyzed amounted to 14 subjects consisting of 81 questions. The instrument used is the documentation of the exam of the semester of the academic year 2015/2016. The data obtained were analyzed by descriptive analysis including data reduction, systematic data presentation, and conclusion drawing. The result of the research shows that the quality of the final exam of the semester of the academic year 2015/2016 in the Biology Education study program is obtained by the low level knowledge aspect of 81.48%, and the high knowledge aspect of 18.52%.